Pendekatan Terintegrasi HTA–HEART dalam Analisis Human Error pada Aktivitas Distribusi PT. Soraya Berjaya Indonesia. Tbk - Anggraini, Denny Astrie; Candra, Yurika Helma (Fakultas Teknik UMRI, 2026)
PT Soraya Berjaya Indonesia Tbk is a company engaged in the production of bedroom equipment. In the process of shipping finished products, various human errors are still found, such as data input errors, discrepancies in the quantity, motif, and size of products, and changes in delivery notes that impact distribution delays and supply chain disruptions. This study aims to identify activities that have the potential to cause human error and determine the probability level of errors in the process of shipping finished products. The method used is Hierarchical Task Analysis (HTA) to identify work activities and Human Error Assessment and Reduction Technique (HEART) to measure the level of human error. The results show that of the 28 sub-tasks analyzed, the activity of filling out the product list along with the number of products transferred and checking the conformity of products with the notes has the highest Human Error Probability (HEP) value of 11.09. This finding indicates that the process of recording and verifying products is the activity with the highest risk of causing errors. Proposed improvements include the implementation of a barcode-based verification system, increasing the stability of the information system network, and strengthening the implementation of Standard Operating Procedures (SOPs). These improvements are expected to reduce the risk of human error and increase the reliability of the finished product distribution process.